Determinan Return Saham Sektor Industri Pertambangan di Indonesia - Aditya Aliyuna; Mahardika Perdanaputra; Hersugondo (Faculty of Economics and Business, University of Pancasakti Tegal, 2022)
The goal of this research is to analyze the determinants of stock return disclosure of mining sector companies listed on the Indonesia Stock Exchange in 2016-2020. In processing the data, this research uses the SPSS 26 program and uses a multiple regression model to verify the relationship between dependent and independent variables. The independent variables profitability ratio (ROA, ROE, ROI), debt to equity ratio (DER), total asset turnover (TATO), oil price and exchange rate. The results of this research shows that profitability ratio (ROA, ROE, ROI) have no effect on stock return, DER in the ROA equation model has no effect on stock returns. Meanwhile, DER in the ROE and ROI equations has a negative effect on stock returns. TATO has no effect on mining company stock returns in all equation models. FOREX / Exchange rate has a negative effect on stock returns of mining companies in all equation models.